The contribution of mechanization to sustainable agricultural development - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1998)
From 24- 29 November 1997, CTA organized an international seminar in Ouagadougou, Burkina Faso, on the integration of mechanization in sustainable agricultural development policy in sub-Saharan Africa